European consumer access to justice revisited / Stefan Wrbka. - Wrbka, Stefan, 1976- (Cambridge University Press, 2015)
European Consumer Access to Justice Revisited takes into account both procedural and substantive law questions in order to give the term 'access to justice' an enhanced meaning. Specifically, it analyses developments and recent trends in EU consumer law and aims to evaluate their potential for increasing consumer confidence in the cross-border market. Via a critical assessment of the advantages and disadvantages of the means initiated at the EU level, the author highlights possible detriments to the cross-border business-to-consumer (B2C) market. To remedy this, he introduces an alternative method of creating a legal framework that facilitates B2C transactions in the EU - 'access to justice 2.0'.